People with severe problematic personality traits and offending histories: What influences occupational participation? - Connell, C (2019)
Background: Occupational participation is important for personality disordered offenders (PDOs) becauseit is integral to health and desistance from offending. What influences occupational participation isunknown for PDOs in the community, limiting effective intervention to affect change. In England andWales, the Offender Personality Disorder Pathway aims to improve outcomes for people consideredhighly likely to have a severe personality disorder and who present a high risk of reoffending, who aredetermined to be PDOs on the basis of a structured assessment. This study identified the influencers ofoccupational participation for the population who receive this service.Method: In this critical realist, qualitative study, narrative interviews were conducted with 18 PDOssupervised by probation in England. Transcripts were analyzed using a grounded theory approach toestablish influencers of occupational participation.Results: Four themes describe influencers of occupational participation: function of occupations;influence of the past; external forces; and learning and adaptation. The latter theme reflectedunderstandings of occupational adaptation described by the Model of Human Occupation.Conclusions: An intervention to increase prosocial occupational participation should be developed andevaluated for PDOs in the community, taking account of occupational participation over the life course